Sensory Evaluation and Antioxidant Activity of Functional Ice Cream with The Ratio of Cardamom Powder and Dragon Fruit Peel Puree - Wahyuniari, Ida Ayu Tisna; Putra, I Gede Arie Mahendra; Devani, Made Dita Dewi; Wiguna, Putu Wedananta Darma; Kartika, Dina Puti (Universitas Ahmad Dahlan, 2025)
Functional food products are emerging due to increased public health awareness. Cardamom (Amomum cardamomum L.), a spice cultivated in Manukaya Village, Bali, is rich in flavonoids and essential oils such as 1,8-cineole, α-terpinyl acetate, α-terpineol, limonene, linalool, and α-pinene. These compounds act as natural flavorings and antioxidants, making cardamom a potential ingredient for functional ice cream. To enhance the ice cream’s appearance, natural colorants like dragon fruit peel waste, which are rich in anthocyanins, can be used. This study contributed to determine the optimal ratio of cardamom powder and dragon fruit peel puree to produce ice cream with favorable characteristics and functional potential. A Randomized Group Design (RGD) was applied with 10 treatment ratios (100:0; 10:90; 20:80; 30:70; 40:60; 50:50; 60:40; 70:30; 80:20; and 90:10) and two replications, totaling 20 experimental units. Ice cream was produced by mixing the ingredients according to each treatment, followed by freezing for 10 hours. The data were analyzed using ANOVA and Tukey’s test. The results indicated that the 10:90 ratio of cardamom powder to dragon fruit peel puree produced the best ice cream, with average sensory scores of 4.82 (slightly liked) for color, 4.65 (slightly liked) for taste, and 4.59 (slightly liked) for overall acceptance. This formulation also showed 20.19% antioxidant activity and had a rosy brown appearance with color values of L* 61.90, a* 10.64, and b* 3.85, supporting its potential as a functional food product.